CoOx nanoparticles embedded in porous graphite carbon nanofibers derived from electrospun polyacrylonitrile@polypyrrole core–shell nanostructures for high-performance supercapacitors. Issue 60 (8th June 2016) - Nie, Guangdi; Lu, Xiaofeng; Chi, Maoqiang; Jiang, Yanzhou; Wang, Ce
Abstract : A novel composite nanostructure of C–CoO x –C with CoO x nanoparticles embedded in N-containing porous graphite carbon nanofibers exhibited a more acceptable specific capacitance, higher rate capability and better cycling stability. Abstract : A novel composite nanostructure of C–CoO x –C with CoO x nanoparticles embedded in N-containing porous graphite carbon nanofibers (CNF) is successfully prepared via sintering the electrospun polyacrylonitrile–cobalt acetate tetrahydrate nanofibers covered by a polypyrrole (PPy) sheath that were attained from the chemical vapor-phase polymerization of pyrrole monomers using concentrated nitric acid as both the dopant and oxidant for the first time. The unique configuration with a well-defined morphology possesses a large specific surface area and prominent conductivity contributed to by the catalysis of metallic Co and the external PPy-derived carbon envelope, which could facilitate effective electron transfer and rapid ion penetration in C–CoO x –C, thus improving its electrochemical performance. As expected, when employed as an electrode active material for supercapacitors, the resultant C–CoO x –C showed a more acceptable specific capacitance, better rate capability and higher cycling stability than individual CNF and CoO x nanoparticle-decorated CNF without the coating of a N-doped carbon layer from PPy (C–CoO x ).